Decoding stratigraphic evolution of the Hailar Basin: Implications for the late Mesozoic tectonics of NE China. (19th July 2019) - Zhu, Ji‐Chang; Meng, Qing‐Ren; Feng, You‐Liang; Yuan, Hong‐Qi; Wu, Feng‐Cheng; Wu, Hai‐Bo; Wu, Guo‐Li; Zhu, Ri‐Xiang
Abstract : The Hailar Basin is located in the northern portion of NE China and preserves relatively complete Middle Jurassic to Cretaceous volcanic and clastic successions. The understanding of the basin's Mesozoic stratigraphic development can help reveal Mesozoic tectonic complexity in NE China. This study focuses on Mesozoic sequences of the Hailar Basin based mainly on interpretations of seismic profiles and logging data. Three tectono‐stratigraphic sequences are dividable, the pre‐Mesozoic, the Middle Jurassic to Lower Cretaceous, and the Upper Cretaceous successions, respectively. Two angular unconformities separate the three sequences, with one below the Middle Jurassic and the other atop the Lower Cretaceous. Noticeable is the absence of the two angular unconformities in the Jurassic to Lower Cretaceous sequence, which are usually observed in the northern North China Block. Instead, a disconformity occurs between the Jurassic and Lower Cretaceous. The absence of angular unconformities in the Hailar Basin implies that this region had not been affected by crustal shortening or the Yanshanian Orogeny that had strongly influenced the northern North China Block in the late Mesozoic. It is concluded that the closure of the Mongol–Okhotsk Ocean exerted little impact on the continent on the south, and flat subducting of the Palaeo‐Pacific Plate might have been responsible for the occurrence of the Yanshan Orogeny.